THE RELATIONSHIP BETWEEN REMEMBERING GOD (DHIKR) AND STRESS PREVENTION OF LIFE PROBLEM - Pauzi, Afi Parnawi, Fithri Mehdini Addieningrum, Neri Aslina, Said Maskur (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Most people on this earth experience stress in their lives. Problems always emerge every day in life. People who are not able to prevent it, it will enter the dimension in which it can bring the soul and become very stressful deeply. Remembering God (Dhikr) practiced by Muslims, in fact, it can prevent and treat stress caused by the life problems. The practice of dhikr is light (calmness) that will brighten him until he is able to give a light to the straight path (The path to get God's guidance). Every person who practice dhikr continuously, it will surely find a peace in its life. It is due to good practice does not find a saturation point. The more you do it, the more it calms down and makes the person to be better. In contrast to bad deeds, although it feels good and easy to be done at the first, but he will find a point of saturation or regret.